Factors Associated with Occurrence of Radiation-induced Optic Neuropathy at "Safe" Radiation Dosage. (19th May 2018) - Doroslovački, Pavle; Tamhankar, Madhura A.; Liu, Grant T.; Shindler, Kenneth S.; Ying, Gui-Shuang; Alonso-Basanta, Michelle
ABSTRACT: Background : Radiation-induced optic neuropathy (RION) is a rare, and often visually devastating, complication of radiation therapy (RT) near the anterior visual pathways. Methods : A retrospective case series of patients who developed RION at a tertiary medical center, followed by a case-control study comparing RION cases with matched controls who received RT. Results : Thirteen patients (18 eyes) with RION were identified. Radiation modalities included external beam photon radiation, whole brain radiation, stereotactic radiosurgery, proton beam, and unknown. Most patients received doses below published "safe" thresholds (<55 Gy; <8–10 Gy for stereotactic radiosurgery). There was no statistically significant difference in prevalence of vasculopathic factors between cases and controls; on subgroup analysis in three patients who received surprisingly low radiation doses, smoking ( p =0.05) and hypertension ( p =0.02) appeared more prevalent. Conclusion : RION can occur at doses below published "safe" thresholds and with different RT modalities. Smoking and hypertension might be risk factors for RION.